Caffeine ingestion does not alter performance during a 100-km cycling time-trial performance - Hunter, A. M.; St. Clair Gibson, A.; Collins, M.; Lambert, M.; Noakes, T. D. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
This study analyzed the effect of caffeine ingestion on performance during a repeated-measures, 100-km, laboratory cycling time trial that included bouts of 1- and 4-km high intensity epochs (HIE). Eight highly trained cyclists participated in 3 separate trials` placebo ingestion before exercise with a placebo carbohydrate solution and placebo tablets during exercise (Pl), or placebo ingestion before exercise with a 7% carbohydrate drink and placebo tablets during exercise (Cho), or caffeine tablet ingestion before and during exercise with 7% carbohydrate (Caf). Placebo (twice) or 6 mg kgÐ1 caffeine was ingested 60 min prior to starting 1 of the 3 cycling trials, during which subjects ingested either additional placebos or a caffeine maintenance dose of 0.33 mg kgÐ1 every 15 min to trial completion. The 100-km time trial consisted of five 1-km HIE after 10, 32, 52, 72, and 99 km, as well as four 4-km HIE after 20, 40, 60, and 80 km. Subjects were instructed to complete the time trial and all HIE as fast as possible. Plasma (caffeine) was significantly higher during Caf (0.43 ± 0.56 and 1.11 ± 1.78 mM pre vs. post Pl; and 47.32 ± 12.01 and 72.43 ± 29.08 mM pre vs. post Caf). Average power, HIE time to completion, and 100-km time to completion were not different between trials. Mean heart rates during both the 1-km HIE (184.0 ± 9.8 Caf; 177.0 ± 5.8 Pl; 177.4 ± 8.9 Cho) and 4-km HIE (181.7 ± 5.7 Caf; 174.3 ± 7.2 Pl; 175.6 ± 7.6 Cho; p < .05) was higher in Caf than in the other groups. No significant differences were found between groups for either EMG amplitude (IEMG) or mean power frequency spectrum (MPFS). IEMG activity and performance were not different between groups but were both higher in the 1-km HIE, indicating the absence of peripheral fatigue and the presence of a centrally-regulated pacing strategy that is not altered by caffeine ingestion. Caffeine may be without ergogenic benefit during endurance exercise in which the athlete begins exercise with a defined, predetermined goal measured as speed or distance.